„S odlišností se nekamarádíme“: Sociální exkluze žáka se speciálními vzdělávacími potřebami v základní škole - Radek Vorlíček (AntropoWebzin)
The purpose of this article is to provide insights into the lives of children in an elementary school classroom in the Slovak Republic. Special attention is paid to the social position of pupils with special educational needs. The text also includes a reﬂection on the roles of researchers in educational settings and on the writing of ﬁeldnotes within the context of a school class. The article is based on qualitative inductive and ethnographic ﬁeldwork. Ethnographic observations play a key role in this ﬁeldwork. The article shows examples of the marginalization and school bullying of a pupil with special educational needs. To some degree, these examples need to be considered in the light of the boundaries of children’s tolerance.